2014
DOI: 10.1097/ta.0b013e3182aa2d21
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome in wartime military burns

Abstract: Epidemiologic/prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 26 publications
0
43
2
3
Order By: Relevance
“…On univariate analysis, the following variables were found to be significantly different among the various categories of ARDS when compared with no ARDS as defined by either definition: increasing age, %TBSA, %FT, II, ISS, 24-hour resuscitation fluid volume >250 ml/kg, AKI score ≥ 1, and pneumonia (Tables 2 and 3). 11,15 This present study suggested, on univariate analysis, a potential link between higher initial resuscitation fluid volume and ARDS, contrary to the previous finding in a military-only cohort. 11,15 However, multiple logistic regression failed to demonstrate an independent relationship between this variable and moderate or severe ARDS ( Table 4).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…On univariate analysis, the following variables were found to be significantly different among the various categories of ARDS when compared with no ARDS as defined by either definition: increasing age, %TBSA, %FT, II, ISS, 24-hour resuscitation fluid volume >250 ml/kg, AKI score ≥ 1, and pneumonia (Tables 2 and 3). 11,15 This present study suggested, on univariate analysis, a potential link between higher initial resuscitation fluid volume and ARDS, contrary to the previous finding in a military-only cohort. 11,15 However, multiple logistic regression failed to demonstrate an independent relationship between this variable and moderate or severe ARDS ( Table 4).…”
Section: Discussioncontrasting
confidence: 85%
“…11,15 This present study suggested, on univariate analysis, a potential link between higher initial resuscitation fluid volume and ARDS, contrary to the previous finding in a military-only cohort. 11,15 However, multiple logistic regression failed to demonstrate an independent relationship between this variable and moderate or severe ARDS ( Table 4). The ARDS Definition Task Force validated the new Berlin definition in a large critical care population.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…27 Despite improvements in patient support, mortality rates from ARDS in the mixed intensive care unit population remain approximately 40%. 28,29 With respect to severe burn, mortality is increased by approximately 20% with inhalation injury and 60% with additional pneumonia, 1 so burn patients with inhalation injury leading to concomitant pneumonia and/or ARDS have a significant risk of complications and demand unique approaches to improve patient care and survival.…”
Section: Discussionmentioning
confidence: 99%
“…In thermally injured patients, inhalation injury is often associated with ARDS, and is an independent predictor of increased morbidity and mortality (20,21). Our goal was to examine the early application of the ECCO 2 R therapy in the setting of mild to moderate ARDS.…”
Section: Introductionmentioning
confidence: 99%